Pertumbuhan Awal Bibit Tanaman Reklamasi di Lahan Bekas Tambang dengan Pemberian Kompos Plus dan Mulsa Alami di Sektor Kalimaya - Rezha Monica Agustina Sinaga; Siman Suwadji; Hastanto Bowo Woesono (Universitas Tanjungpura, 2023)
Mining in Indonesia uses an open pit mining system that has the potensial to cuase loss of forest vegetation and damage to the physical, chemical and biological properties of the soil. This soil damage result in former mining land to be nutrient poor so that it requires a supply of nutrients form outside in order to support plant growth. The purpose of this study was to determine the effect of the use of compost plus and natural mulch on the growth of reclaimed plants in the former mining land. The research was conducted in the post-mining area of PT Asmin Bara Bronang, Sektor Kalimaya, Kabupaten Kapuas, Kalimantan Tengah. The study used a two-factor complete randomized design (RAL) with two repetitions. The first factor is the type of plant (T); Johar (T1), Sengon (T2), and Bintaro (T3). While the second factor is compost plus ± mulch (p): P1 (control treatment), P2 (using compost plus without mulch) and P3 (combination of compost plus and mulch). The results showed that the treatment of plant species does not affect the height of the plant but significantly affect the diameter of the STEM and the number of leaves, while the treatment of compost and mulch significantly affect the plant height, stem diameter and number of leaves. The best results of measuring plant growth parameters were obtained from the combination of compost plus and mulching treatment (P3).Keywords: compost plus, natural mulch, growth, reclamation plants, ex-mining land.